2003
DOI: 10.1194/jlr.m300089-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols in low- and nonfat beverages as part of a controlled diet fail to lower plasma lipid levels

Abstract: Dietary phytosterols have been shown to reduce plasma cholesterol concentrations when consumed in different food matrices, but their effectiveness in nonfat or low-fat beverages has not been established. The objective of this study was to examine whether phytosterols alter plasma lipid levels when incorporated into nonfat or low-fat beverages. Fifteen moderately hypercholesterolemic men and women consumed three precisely controlled diets for periods of 21 days each in random order. Diets contained either a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 37 publications
4
65
1
Order By: Relevance
“…Analyses were conducted as part of a study from which data on plasma lipid levels have already been reported (Jones et al, 2003). Briefly, 15 healthy volunteers (nine men, six women), aged between 22 and 68 y, with LDL-cholesterol between 3.25 and 6.0 mmol/l, high-density lipoprotein (HDL) cholesterol above 0.8 mmol/l, triglycerides (TG) concentrations below 4.0 mmol/l and body mass index (BMI) between 22 and 32 kg/m 2 were recruited as described previously (Jones et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analyses were conducted as part of a study from which data on plasma lipid levels have already been reported (Jones et al, 2003). Briefly, 15 healthy volunteers (nine men, six women), aged between 22 and 68 y, with LDL-cholesterol between 3.25 and 6.0 mmol/l, high-density lipoprotein (HDL) cholesterol above 0.8 mmol/l, triglycerides (TG) concentrations below 4.0 mmol/l and body mass index (BMI) between 22 and 32 kg/m 2 were recruited as described previously (Jones et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 15 healthy volunteers (nine men, six women), aged between 22 and 68 y, with LDL-cholesterol between 3.25 and 6.0 mmol/l, high-density lipoprotein (HDL) cholesterol above 0.8 mmol/l, triglycerides (TG) concentrations below 4.0 mmol/l and body mass index (BMI) between 22 and 32 kg/m 2 were recruited as described previously (Jones et al, 2003). Individuals reporting a personal endocrine disorder, dyslipidemia, hypertension, familial sitosterolemia, gastrointestinal disorders, iliac bypass surgery, heart disease or unstable angina in the last 3 months prior to screening were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations